PERANCANGAN SISTEM PISAU PADA MESIN PENGIRIS BAWANG MERAH DAN BAWANG BOMBAY TENAGA HYBRID - Irawan, Muhammad Hafizh Putra; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2024)
This shallot and onion slicing hybrid power machine functions in one tool, the machine operates using an electric power source and in the event of a power outage, this machine can still operate because it is equipped with additional electricity sourced from battery batteries. The resulting ability of the onion and onion slicing machine with a single-phase motor power that has 2800 rpm and also two onion slicing blades and one onion slicing blade, the average time required from slicing shallots is 30 seconds or 0.5 minutes with 250 grams of shallots while for onions is 164.2 seconds or 2.7 minutes with 250 grams of onions one or two. Maintenance is also very easy and can be disassembled starting from the plate and also the knife blade, then the cover or cover of the machine that can be removed to facilitate the cleaning process by washing or cleaning from the remaining onion skin and also unnecessary objects.